Limits to green revolution in rice in Africa: The case of Ghana - Ragasa, Catherine; Chapoto, Antony (International Food Policy Research Institute, 2016)
This paper examines closely the constraints in productivity improvements and evaluates available rice technologies looking at the heterogeneity of irrigated and rainfed ecologies in 10 regions in Ghana. Employing yield response models, profitability analysis, and adoption models, results show various practices contribute to yield improvements in irrigated and rainfed systems including chemical fertilizer use, use of certified seed of improved varieties, transplanting, bunding, leveling, use of a sawah system, seed priming, and row planting. Evidence also shows that extension services on rice production are limited and that intensifying extension services can contribute to increases in rice yield.